Electronic structure and transport properties of CeNi9In2. (March 2015) - Kurleto, R.; Starowicz, P.; Goraus, J.; Baran, S.; Tyvanchuk, Yu.; Kalychak, Ya. M.; Szytuła, A.
Abstract: We investigated CeNi9 In2 compound, which has been considered as a mixed valence (MV) system. Electrical resistivity vs. temperature variation was analyzed in terms of the model proposed by Freimuth for systems with unstable 4f shell. At low temperature the resistivity dependence is consistent with a Fermi liquid state with a contribution characteristic of electron–phonon interaction. Ultraviolet photoemission spectroscopy (UPS) studies of the valence band did not reveal a Kondo peak down to 14 K. A difference of the spectra obtained with photon energies of low and high photoionization cross sections for Ce 4f electrons indicated that 4f states are located mainly close to the Fermi energy. The peaks related to f5/2 1 and f7/2 1 final states cannot be resolved but form a plateau between −0.3 eV and the Fermi energy. X-ray photoemission spectroscopy (XPS) studies were realized for the cerium 3d level. The analysis of XPS spectra within the Gunnarsson-Schönhammer theory yielded a hybridization parameter of 104 meV and non-integer f level occupation, being close to 3. Calculations of partial densities of states were realized by a full potential local orbital (FPLO) method. They confirm that the valence band is dominated by Ni 3d states and are in general agreement with the experiment except for the behavior of f-electrons. Abstract : Highlights: UPS studies of CeNi9 In2 revealed that the Kondo peak is not visible down to 14 K. Ce 4f related spectrum shows a plateau between 0.3 eV and the Fermi energy. Low temperature electrical resistivity is compatible with a Fermi liquid model with lattice contribution. Higher temperature resistivity can be fitted to the model for unstable valence systems.